Effectiveness of Objective Structured Practical Examination (OSPE) as a Tool for Formative Assessment of Practical and Experimental Skill for Pre-University Students in Biology Course - Rohaiza, Daud; Mohamad Fhaizal, Mohamad Bukhori; Christharina, S Gintoron; Mohamad Razif, Othman; Roberta Chaya Tawie, Tingga; Muhamad Ikhwan, Idris; Mohd Aminuddin, Mustapha; Maybelline Goh, Boon Ling; Norfarahin, Norwen (UNIMAS Publisher, 2023)
In many science courses or subjects, lectures (theory) and practical (hands-on) are integrated with the view that theory can be explained in the lecture and then applied and tested in the practical class (Whitworth & Wright, 2015). Similarly, in the Biology course for Centre for Pre- University Studies, Universiti Malaysia Sarawak, a lecture on Introduction to Laboratory Instrumentation was conducted. Meanwhile, the practical application and demonstration for this topic were also carried out. The objectives for this practical are to describe the usage and to define the functions of basic laboratory equipment and apparatus as well as to demonstrate the correct way of handling basic laboratory equipment and apparatus.